2003
DOI: 10.1074/jbc.m209805200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the Ras-GRF1 Exchange Factor at Ser916/898 Reveals Activation of Ras Signaling in the Cerebral Cortex

Abstract: The Ras-GRF1 exchange factor, which is regulated by increases in intracellular calcium and the release of G␤␥ subunits from heterotrimeric G proteins, plays a critical role in the activation of neuronal Ras. Activation of G protein-coupled receptors stimulates an increase in the phosphorylation of Ras-GRF1 at certain serine residues. The first of these sites to be identified, Ser 916 in the mouse sequence (equivalent to Ser 898 in the rat sequence), is required for full activation of the Ras exchange factor ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 66 publications
1
41
1
2
Order By: Relevance
“…Previous studies have suggested that the Rem domain of RasGRF1 is regulatory in function, containing phosphorylation sites and PEST motifs (25)(26)(27)(28). The level of activity we observe for the isolated Cdc25 domain of RasGRF1, although significantly greater than the intrinsic rate of nucleotide release from Ras, is much lower than the maximum rate observed for allosterically activated Sos cat .…”
Section: Discussioncontrasting
confidence: 43%
“…Previous studies have suggested that the Rem domain of RasGRF1 is regulatory in function, containing phosphorylation sites and PEST motifs (25)(26)(27)(28). The level of activity we observe for the isolated Cdc25 domain of RasGRF1, although significantly greater than the intrinsic rate of nucleotide release from Ras, is much lower than the maximum rate observed for allosterically activated Sos cat .…”
Section: Discussioncontrasting
confidence: 43%
“…Plasmids encoding the same inserts with enhanced green fluorescent protein (GFP) replacing the HA1 epitope tags were prepared by subcloning BamHI/EcoRI fragments into the pRK7sGFP vector (Carey et al, 1996). A plasmid encoding the ⌬N mutant fused to glutathione S-transferase (GST) has previously been described (Yang et al, 2003). Similar constructs expressing the ⌬C mutant or Rac1 were prepared by subcloning the relevant BamHI/EcoRI fragments into pGEX-2T.…”
Section: Plasmidsmentioning
confidence: 99%
“…Transfected PC12 cells were fixed and processed for confocal indirect and GFP fluorescence broadly as previously described (Yang et al, 2003), with the following modifications: The primary antibodies used were anti-Myc monoclonal antibody (mAb) 9e10 (1:1000 dilution; Sigma) for detection of cells expressing Myc-tagged Ras or Rac proteins, anti-Ras-GRF1 polyclonal antibody sc224 (1:500 dilution; Santa Cruz Biotechnology, Santa Cruz, CA) to detect untagged Ras-GRF1, anti-Flag mAb M2 (1:200 dilution; Sigma) to detect Flag-tagged MEK1.K97M, and either anti-hemagglutinin-1 (HA1) polyclonal antibody Y-11 (1:150 dilution; Santa Cruz) or 12CA5 mAb (1:500) for detection of cells expressing HA1 3 -tagged proteins. For detection of neurofilaments, mAb RT97 (NICHD Developmental Studies Hybridoma Bank, Iowa City, IA) was used at a 1:100 dilution.…”
Section: Confocal Immunofluorescencementioning
confidence: 99%
See 1 more Smart Citation
“…79 Moreover, phospho-specific antibodies to this site in GRF1 demonstrated that this site does get phosphorylated in the dendrites of cortical neurons in the brain, implying that this phenomenon plays some role in synaptic plasticity. 80 Interestingly, this site on GRF1 was shown to become phosphorylated in response to signals that induce LTP in the CA1 region of the hippocampus. 81 This event was shown to involve CamKI, although PKA was likely the enzyme that directly phosphorylates GRF1.…”
Section: Pka and Camkimentioning
confidence: 99%